Recurrence of plexiform ameloblastoma as acanthomatous ameloblastoma: A rare case report - Sanat Kumar Bhuyan; Ruchi Bhuyan; Tapan Kumar Sahoo; Pinali Das (Wolters Kluwer Medknow Publications, 2019)
Ameloblastoma is an uncommon locally invasive benign odontogenic tumor arising from the odontogenic epithelium. It is a slow-growing tumor with locally aggressive nature, and posterior mandible is the most common location. The recurrence rate is high even after en bloc resection. Acanthomatous ameloblastoma is one of the rare variants of ameloblastoma and is usually seen in older age group. Here, we present a case of acanthomatous ameloblastoma in a 46-year-old female who previously diagnosed and treated for a case of plexiform ameloblastoma 17 years back. This is the first case to be reported among ameloblastoma with different histopathological variants at recurrence.